Evaluation of Some Biochemical Parameters in Haemolymph of Bulinus specie in Ajiwa Reservoir Katsina State, Nigeria - Usman, L. U.; Adakole, J. A.; Gadzama, I.M.K.; Sama’ila, A. U. (UMYU Journal of Microbiology Research, 2016)
Evaluation of some biochemical parameters was conducted in haemolymph of Bulinus sp in Ajiwa reservoir, Katsina state, Nigeria from September, 2014 to August, 2015. Four samples of Bulinus spwere collected at 5 different sampling locations every 3 months and were transferred into labelled plastic storage bottle and transported into laboratory for haemolymph extraction and analysis. Glucose, Aspartate amino transferase (AST) and Alanine amino transferase (ALT) were determined using standard methods, procedures and instruments. The mean value of the biochemical parameters are Glucose (36.28±1.76mg/dl), AST (19.21±0.24U/L) and ALT (13.91±0.62U/L). The level of the parameters were slightly increasing in the following order of magnitude; station 3 > station 2 > station 4> station 1 and station 5 recorded the lowest value. Seasonal variation of the biochemical parameters were clearly observed in the Bulinus sp. Glucose, AST and ALT levels were higher during the wet season compared to dry season (45.83±1.83mg/dl to 27.49±0.93mg/dl), (24.61±0.16 to 13.80±0.13U/L) and (19.33±0.78 to 10.44±0.21U/L) respectively. This may be due to high influx of nutrients from the surrounding farm lands and other domestic activities like bush burning, washing clothes, bathing and cattle rearing within the vicinity of the reservoir. Alterations in these biochemical parameters (Glucose, AST and ALT) in the haemolymph, indicate disturbance of the oxidative carbohydrate and protein metabolism. Apart from evaluating energy content as biomarkers, this experiment shows how Bulinus sp undergoes metabolic alteration to overcome stress.